Impact of Exercise and Physical Activity on Symptom Management in Children with Attention Deficit Hyperactivity Disorder (ADHD) - Goswami, Jayeeta; Dixit, Preeti (Stallion Journal for Multidisciplinary Associated Research Studies, 2022)
The purpose of this study is to examine the possibility of structured exercise and physical activity programs as non-pharmacologic interventions of ADHD symptoms in children. In relation to the complex interplay of neurological, behavioural and psychological factors present in ADHD, the research follows a controlled experimental design alongside a 12 weeks tailored 12 weeks physical activity regimen with rigorous test of attenuation of the main symptoms of ADHD as attention deficit, hyperactivity and impulsivity. The participants of the study included children with a diagnosis of ADHD between the ages of 6 and 12 who were randomly assigned to an intervention group in a structured physical activity, or a control group with no intervention. The exercise program included a number of aerobic, strength training and game activities that are meant to engage kids in activities that will enhance focus, behaviour and emotional regulation. Children and staff were followed by trained professionals, together with parental and teacher reports at baseline and at the conclusion of the program, for who were measured using a combination of psychometric assessments and behavioural observations. this abstract gives a detailed synopsis of what the study centres on, how it is done, what the key outcomes are, and what is the implications of the findings in the larger picture.